The Relationship of Personality Factors and General Self-Efficacy with Operative and Strategic Hope for Treatment in Addicts - fatemeh dehghan; hamid atashpour; abbas shafti (Drug Control Headquarters, Research and Education Office, 2015)
Objective: The aim of this study was to determine the relationship of personality factors and general self-efficacy with operative and strategic hope for treatment. Method: The number of 350 self-referred addicts to treatment centers in Isfahan City was chosen through random cluster sampling. Then, the three following questionnaires entitled personality traits of NEO, Sherer and Maddux's General Self-Efficacy Scale, and Schneider Adult Hope Scale were administered to them. Results: The results showed that personality factors and general self-efficacy were correlated with hope for treatment. As well, dimensions of neuroticism and conscientiousness, and by far, self-efficacy had the predicative power of hope for treatment. Conclusion: Personality factors and general self-efficacy are useful for the estimate of operative and strategic hope for treatment in addicts.